2012
DOI: 10.3113/fai.2012.1051
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Location and Morphology of Symptomatic, Operatively Treated Osteochondral Lesions of the Talus

Abstract: With regard to symptomatic, operatively treated OCLTs, the results of the current study parallel current evidence that posteromedial and anterolateral OCLTs are not the most common locations of OCLTs. As well, medial OCLTs were larger in surface area than lateral OCLTs, but no differences existed with regard to lesion depth. It is interesting that operatively treated OCLTs were twice as commonly located in the centrolateral third rather than the centromedial third of the talar dome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 30 publications
(58 reference statements)
3
23
0
Order By: Relevance
“…Some previous authors have reported more distributions of medial lesions compared with lateral ones [12,19,20,24]. On the contrary, Justin D. Orr et al [25] reported that operatively treated OLTs were mainly located in the lateral zones, based on 68 cases all under 60 years old. A systemic review [26] of 32 studies reported that 44 % of lesions were lateral and 56 % were medial.…”
Section: Discussionmentioning
confidence: 93%
“…Some previous authors have reported more distributions of medial lesions compared with lateral ones [12,19,20,24]. On the contrary, Justin D. Orr et al [25] reported that operatively treated OLTs were mainly located in the lateral zones, based on 68 cases all under 60 years old. A systemic review [26] of 32 studies reported that 44 % of lesions were lateral and 56 % were medial.…”
Section: Discussionmentioning
confidence: 93%
“…Analysing the results of variations in the defect size, it seems that positive defects, which may occur in the stage IV lesions ( i.e. , detached and displaced osteochondral fragment) [ 23 ], made noticeable alterations to the output signal, whereas, negative defects ( Figure 2 ) created relatively small changes ( Figures 8 and 9 ). Increasing the width for negative talus defects did not seem to vary the output signal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the defects with negative depth values, positive defects ( Figure 2 ), which may occur in the stage IV lesions ( i.e. , detached and displaced osteochondral fragment) [ 23 ] were considered. Throughout the simulations, the size of temporal and spatial domain, the grid size, the boundary conditions, and the material properties were kept identical to the reference model.…”
Section: Methodsmentioning
confidence: 99%
“…OLT dimensions (anteroposterior and transverse diameters and depth) based on T1-weighted MRI were determined in accordance with previously described techniques. 18,19 MRI assessments, including localization, quantification of measurements, and staging classification, were performed by a board-certified orthopaedic surgeon not involved in the operations. Preoperative computed tomography (CT) imaging ( Figure 1C) was performed in all 8 cases to further assess lesion morphology.…”
Section: Methodsmentioning
confidence: 99%